Black Lives Matter! Nigerian Lives Matter!: Language and Why Black Performance Matters - Abimbola A. Adelakun (Genealogy)
This essay explores performance as a language by looking at its appropriation by other cultures, and the associated history of the crafted phrases that are borrowed along. I start by noting that to create awareness of the massacres that have recently occurred in some parts of Nigeria, commentators, both in and out of the country, and activist-cum-protesters created the term “Nigerian Lives Matter.„ They appropriated from “Black Lives Matter,„ the American-originated advocacy movement that campaigns against violence and brutality against black people. I show that these forms of lexical interchange are possible because of non-Americans’ familiarity with America’s racial history, and black performance liberation expressivity, which they have been acculturated into as a result of their long exposure to American culture. Beyond phrases however, I argue that black performance itself is a language that has a global resonance among minorities. To illustrate this further, I do a close reading of This is Nigeria, a recent music video released by Nigerian lawyer turned artist, Folarin Falana (Falz), alongside a version of the original production, This is America, also recently released by Donald Glover (Childish Gambino). Both songs continue in the older tradition of African and African American transatlantic political relations through music, the shared understanding of the similarities of anti-black oppression, and the formation of aesthetics that mediate the advocacy of black liberation. The songs are also a pointer to how black advocacy might continue to unfold in contemporary era.